Examining the Relationship Between Solvent Variations and Oil Yield in Avocado Pear Seed Extraction - Iheme Chigozie; Nnadikwe Johnson; Joy Chinemerem Johnson; Mbadike Columbus Asodike (BIOS: Jurnal Informatika dan Sains, 2025)
This study investigated the effect of solvent variations on oil yield in avocado pear seed extraction. Avocado seeds were dried, ground, and extracted using Soxhlet apparatus with three different solvents: petroleum ether, normal hexane, and methylene chloride. The extraction process was carried out at different temperatures (50°C, 60°C, and 70°C) for 2 hours each. The oil yield was calculated and compared among the three solvents.Results showed that methylene chloride solvent produced the highest oil yield, followed by petroleum ether, while normal hexane yielded the least. However, there was no significant difference in oil yield between petroleum ether and normal hexane. The findings suggest that solvent variation significantly affects oil yield in avocado pear seed extraction, and methylene chloride is the most effective solvent for optimal oil yield..